Optical Forces Acting on a Double DNA-Like Helix, Its Unwinding and Strands Rupture - Igor V. Semchenko; Ivan S. Mikhalka; Ihar A. Faniayeu; Sergei A. Khakhomov; Aliaksei P. Balmakou; Sergei A. Tretyakov (Photonics, 2020)
In this paper we study electromagnetic forces induced on DNA and DNA-like helices by external electromagnetic waves. We consider simultaneously occurring forces and torques, interconnected and acting along the double helix axis. Since the DNA molecule has an absorption band in the ultraviolet and visible range near wavelengths <semantics>λ1res=280</semantics> nm and <semantics>λ2res=500</semantics> nm, we expect that it may be possible to selectively apply engineered forces to DNA molecules using appropriate illumination by light in these frequency ranges. The optical forces are simulated for DNA fragments consisting of 20 and 35 turns. Fragments of this length are convenient for direct sequencing and subsequent use in experiments and in practice. It is shown that repulsion forces can arise between the strands of the double DNA-like helix in the field of external electromagnetic waves. Such forces are characteristic of a DNA-like helix with its specific pitch angle and are not inherent in double helices with more straightened or more compressed turns. These repulsion forces, acting along the entire helix, both for electric charges and for electric currents, can lead to damage and rupture of the strands in the double helix. In addition, there can also exist forces and moments of forces directed along the helix axis, which simultaneously stretch and unwind a double helix. The double helix equilibrium under the action of optical forces is also of interest from another point of view, i.e., for optimizing the structure of artificial magnetics and bianisotropic metamaterials for applications in all frequency ranges.